“Jeg er altid Herman Lynges Ven og Client!” C.F. Wegener som biblioteksbygger - Larsen, Svend (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
C.F. Wegener (1802–1893) was a Danish historian and archivist. His activities as historian and as leader of the Danish national archives (1848–1882) are well known and described in literature. Wegener is also known as owner of a big private library, and he is one the very few Danish book collectors who had built a separate building for his collection. Wegener’s library was bought by the state in 1898 to be transferred to the new State Library in Aarhus which was being built at the time. The 40.000 volumes are still housed in the State and University Library. There is a printed catalogue of the library Bibliotheca Wegeneriana (1897; 4 vol.). It has a short introduction by Christian Bruun, head of the Royal Library, who had known Wegener. But otherwise Wegener’s activities as a library builder have not been described. This article is an attempt to remedy this. The articles is based on the 573 letters Wegener sent to his preferred bookseller Herman H. J. Lynge (1822–1897). The letters (now in the Royal Library) were written between 1853 and 1891 and they give insight in the character of Wegener’s book collecting.